Generation and Characterization of Stable Small Colony Variants of USA300 Staphylococcus aureus in RAW 264.7 Murine Macrophages - Dalida Bivona; Carmelo Bonomo; Lorenzo Colombini; Paolo G. Bonacci; Grete F. Privitera; Giuseppe Caruso; Filippo Caraci; Francesco Santoro; Nicolò Musso; Dafne Bongiorno; Francesco Iannelli; Stefania Stefani (MDPI AG, 2024)
Intracellular survival and immune evasion are typical features of staphylococcal infections. USA300 is a major clone of methicillin-resistant S. aureus (MRSA), a community- and hospital-acquired pathogen capable of disseminating throughout the body and evading the immune system. Carnosine is an endogenous dipeptide characterized by antioxidant and anti-inflammatory properties acting on the peripheral (macrophages) and tissue-resident (microglia) immune system. In this work, RAW 264.7 murine macrophages were infected with the USA300 ATCC BAA-1556 S. aureus strain and treated with 20 mM carnosine and/or 32 mg/L erythromycin. Stable small colony variant (SCV) formation on blood agar medium was obtained after 48 h of combined treatment. Whole genome sequencing of the BAA-1556 strain and its stable derivative SCVs when combining Illumina and nanopore technologies revealed three single nucleotide differences, including a nonsense mutation in the shikimate kinase gene aroK. Gene expression analysis showed a significant up-regulation of the uhpt and sdrE genes in the stable SCVs compared with the wild-type, likely involved in adaptation to the intracellular milieu.